Sustainable Entrepreneurship:A Bibliometric Analysis of Digital Marketing Trends - Zrybnieva, Iryna (Futurity Economics&Law, 2023)
This research aims at how important digital marketing is for encouraging sustainable business, focusing on global trends, country-specific strategies, and the use of new technologies. The goal of this study is to explore academic papers that discuss about how sustainable business and digital marketing can work together, directing on big economies like the G7, China, and India. A mixed-method approach was used, which included bibliometric analysis, and document analysis. 80 scientific papers were used to collect data, and the PRISMA method was used to make sure that the review process was organised and clear. The main results show that digital marketing tools like content marketing, search engine optimization (SEO), and social media are very important for making sustainable business practices more visible and having a bigger effect. Getting people to care about sustainability and interact with brands is especially easy through social media and influencer marketing. AI and big data analytics are widely used in G7 countries to improve marketing strategies and reach people who care about the environment. China focusses on e-commerce and mobile technologies, while India uses social media and local influencer marketing to reach a wide range of people. New technologies like AI and big data analytics are changing digital marketing strategies. They give marketers more information about how customers behave and let them make more personalized campaigns. This study is useful because it explores how digital marketing strategies can be used to reach sustainability goals in a thorough way. The results are useful for researchers, policymakers, and businesspeople who want to combine digital marketing with sustainable entrepreneurship. Businesses can improve their efforts to be sustainable, connect with customers more effectively, and build a strong brand presence that cares about social and environmental issues by understanding and using these strategies.
Keywords: Artificial intelligence; Big data analytics; Consumer engagement; Digital marketing; Sustainability; Entrepreneurship